Don't let go [compact disc, unabridged] - Coben, Harlan, 1962- (Brilliance Audio, 2017)
For fifteen years, suburban New Jersey detective Napoleon Dumas has been searching for Maura, the love of his life who disappeared without explanation, and for the real reason behind his brother's death. And now it looks as though he may have finally found what he's been looking for.